1981
DOI: 10.1111/j.1399-3054.1981.tb06054.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental UV‐B radiation on growth and leaf photosynthetic reactions of soybean (Glycine max)

Abstract: 1981, Effects of supplemental UV-B radiation on growth and leaf photosynthetic reactions of soyhean (Glycine max). -Physiol. Plant. 52: 353-362.Experiments were conducted under greenhonse conditions to investigate the effects of enhanced UV-B radiation (280 to 320 nm) OB height, fresh and dry weights, leaf chlorophyll and carotenoids, CO^ uptake rates, and Hill activity in soybean {Glycine max L. cv. Bragg). Plants were exposed for 6 h continuously from midmorning to midafternoon each day to UV-B radiation whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 19 publications
6
32
0
Order By: Relevance
“…2C), it is concluded that higher UV-B radiation (16 kJ m −2 per day) has both direct and indirect effects on cotton leaf photosynthesis. Similar reductions in photosynthesis were observed in other crop species such as soybean (Vu et al, 1981) and rice (Teramura et al, 1990). Nogues et al (1999) also reached a similar conclusion that there is a direct effect of UV-B radiation on stomatal conductance in addition to that caused by changes in mesophyll photosynthesis of pea, Asiatic dayflower (Commelina communis L.), and oilseed rape (Brassica napus L.) plants.…”
Section: Temporal Photosynthesis Trendssupporting
confidence: 60%
See 1 more Smart Citation
“…2C), it is concluded that higher UV-B radiation (16 kJ m −2 per day) has both direct and indirect effects on cotton leaf photosynthesis. Similar reductions in photosynthesis were observed in other crop species such as soybean (Vu et al, 1981) and rice (Teramura et al, 1990). Nogues et al (1999) also reached a similar conclusion that there is a direct effect of UV-B radiation on stomatal conductance in addition to that caused by changes in mesophyll photosynthesis of pea, Asiatic dayflower (Commelina communis L.), and oilseed rape (Brassica napus L.) plants.…”
Section: Temporal Photosynthesis Trendssupporting
confidence: 60%
“…necrotic patches could be attributed to the decrease in leaf chlorophyll content (up to 40%) on exposure to UV-B, which is widely reported (Smith et al, 2000;Strid and Porra, 1992;Vu et al, 1981).…”
Section: Effect Of Uv-b On Cotton Morphologymentioning
confidence: 67%
“…It has been demonstrated that UV-B radiation can decrease Hill reaction activity (3, 29,30) and variable fluorescence (13,19 In addition to nonstomatal conductance, a significant decrease in stomatal conductance followed UV-B irradiation. Although stomatal conductance accounted for only one-third of the total leaf diffusive conductance, it was highly correlated with the decrease in photosynthesis (r = 0.78, P < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…UV-B radiation may irreversibly damage PSII reaction centers (13,21,23) and such damage could be observed in reduced AQE or substrate regeneration limitations since the energy produced by the light reaction products (e.g. NADPH, ATP) is required to regenerate substrate.…”
Section: Discussionmentioning
confidence: 99%